The association of metabolic syndrome with the characteristics of colorectal adenomas - Damjanov, Dimitrije; Savić, Željka; Latinović Bošnjak, Olgica; Krnetić, Žarko; Vračarić, Vladimir; Janjić, Nebojša; Dejanović, Božidar (Vojnosanitetski pregled, 2025)
Background/Aim. Metabolic syndrome (MetS) is associated with an increased risk of developing colorectal cancer (CRC). However, data on its relationship with colorectal adenomas (CRA), the primary precancerous lesions, remain unclear and limited in certain regions. The aim of this study was to examine the characteristics and distribution of CRA in patients with and without MetS. Methods. A cross-sectional study was conducted, including 80 patients with CRA, of whom 40 had MetS (MetS group), and 40 did not meet the criteria for MetS (control group). Demographic data, risk factors for CRC (smoking, alcohol consumption, and family history of CRC), protective factors (use of acetylsalicylic acid and nonsteroidal anti-inflammatory drugs, physical activity), and polyp characteristics (size, number, localization, and degree of advancement) were collected and compared between the two groups. The diagnosis of CRA was established by histological examination of polyp specimens retrieved during colonoscopy. The diagnosis of MetS was made if three or more of the following criteria were present: increased waist circumference (≥ 94 cm for males, or ≥ 80 cm for females); hypertriglyceridemia (≥ 1.7 mmol/L); reduced high-density lipoprotein cholesterol levels (< 1.0 mmol/L for males, or < 1.3 mmol/L for females); arterial hypertension (systolic blood pressure ≥ 130 mmHg, and/or diastolic blood pressure ≥ 85 mmHg); fasting hyperglycaemia (≥ 5.6 mmol/L). Results. The average age of the patients was 61 years. Males and females were equally present in both groups, as were all the common risk factors for CRA. There were no differences between the groups regarding adenoma size, number of detected adenomas, localization of adenomas, and the degree of histological advancement of the adenoma. Conclusion. No significant association was found between the presence of MetS and the characteristics and distribution of CRA in our study. Further studies with larger samples and biomarker analyses are needed to better understand the potential role of MetS-related factors in colorectal carcinogenesis.
Keywords: adenoma; colon; colorectal neoplasms; metabolic syndrome; polyps; risk factors